A New Analytical Bench Assay for the Determination of Arylsulfatase A Activity Toward Galactosyl-3-Sulfate Ceramide: Implication for Metachromatic Leukodystrophy Diagnosis - Morena, Francesco; di Girolamo, Ilaria; Emiliani, Carla; Gritti, Angela; Biffi, Alessandra; Martino, Sabata (Analytical chemistry (Washington), 2014)
Here, we present the design and validation of a new assay for the diagnosis of metachromatic leukodystrophy. The method is highly specific, simple, reproducible, and straightforward. In our spectrophotometric method, the determination of arylsulfatase A (ARSA) activity toward the natural substrate, galactosyl-3-sulfate ceramide (or sulfatide), is performed using neat sulfatide without chemical modification. This confers to the assay high analytical specificity. The hydrolyzed sulfatide is monitored upon inclusion of the colorimetric reagent Azure A. The nonhydrolyzed sulfatide-Azure A is recovered and measured at a wavelength of λ = 650 nm. Thus, ARSA activity toward the sulfatide is obtained by subtracting the nonhydrolyzed sulfatide from the total sulfatide used in the enzyme reaction (sulfatide-Azure A present in a parallel assay performed in the absence of ARSA). Within a clinical context, our method definitely discriminated between healthy subject samples and metachromatic leukodystrophy patient samples, and, therefore, it is suitable for diagnostic applications and for monitoring the efficacy of therapeutic treatments in patients or animal models.